The interaction between age and parity on adverse pregnancy and neonatal outcomes - Dai, Jiayang; Shi, Ya; Wu, Yinshuang; Guo, Lu; Lu, Dan; Chen, Ying; Wang, Yuanyuan; Lai, Hanpeng; Kong, Xiang (Frontiers in Medicine, 2023)
Background Although age and parity are recognized as associated factors for adverse pregnancy outcomes, there are no studies exploring the interaction between the two during pregnancy. This study aimed to investigate the impact of the interaction between age and parity on adverse pregnancy outcomes. Methods This was a retrospective cohort study with 15,861 women aged ≥20 years. All women were grouped according to age, parity, and a mix of the two. The data were analyzed using multivariate logistic regression analysis. Results: Age, parity, and interaction between the two were related with the risk of gestational hypertension, eclampsia/preeclampsia, placenta previa, placental implantation, postpartum haemorrhage, preterm birth, caesarean section and Apgar score <7 within 5 minutes of birth. The risk of gestational diabetes mellitus and transfer to the neonatal unit was linked with age and the interaction between age and parity, but the impact of parity was not statistically significant. The risk of anaemia, placental abruption, premature rupture of the membrane, oligohydramnios and macrosomia was only associated with parity; the risk of fetal distress was only associated with age. Conclusion The interaction between advanced age and parity might result in more adverse outcomes for both puerpera and infants, necessitating additional prenatal screening and health education throughout pregnancy.